2010
DOI: 10.1016/j.ajhg.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Robust Replication of Genotype-Phenotype Associations across Multiple Diseases in an Electronic Medical Record

Abstract: Large-scale DNA databanks linked to electronic medical record (EMR) systems have been proposed as an approach for rapidly generating large, diverse cohorts for discovery and replication of genotype-phenotype associations. However, the extent to which such resources are capable of delivering on this promise is unknown. We studied whether an EMR-linked DNA biorepository can be used to detect known genotype-phenotype associations for five diseases. Twenty-one SNPs previously implicated as common variants predispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
211
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 273 publications
(215 citation statements)
references
References 33 publications
4
211
0
Order By: Relevance
“…Algorithms were then assessed by calculating PPV, NPV, sensitivity, and specificity as well as evaluating the associations between patient characteristics and indications for imaging with fibroid risk. [11][12][13] Indications for pelvic imaging were determined by manual review of participants EMR. All indications were collected and those reported are the most common indications across records.…”
Section: Figmentioning
confidence: 99%
“…Algorithms were then assessed by calculating PPV, NPV, sensitivity, and specificity as well as evaluating the associations between patient characteristics and indications for imaging with fibroid risk. [11][12][13] Indications for pelvic imaging were determined by manual review of participants EMR. All indications were collected and those reported are the most common indications across records.…”
Section: Figmentioning
confidence: 99%
“…However, Tessier-Sherman and colleagues found that a carefully constructed algorithm for identifying hypertensive patients from claims data only found 43-61% of patients with elevated blood pressure values in their medical charts [25]. Ritchie et al describe a solution for this problem, which consists of a sophisticated, iterative approach to algorithm construction [26]. In their approach, clinical experts are consulted to develop an algorithm that selects cases via disease-specific combinations of billing codes, patient encounters, laboratory data, and NLP techniques on unstructured patient records.…”
Section: Patient Selection From Ehr and Administrative Datamentioning
confidence: 99%
“…Another example are the measures available within EHR, where patients have collections of International Classification of Disease (ICD) billing codes, free text, longitudinal clinical laboratory variable measures, and imaging data. To date, ICD-9 codes and phenotyping algorithms have both shown utility in association studies [20][21][22][23] .…”
Section: Phenomicsmentioning
confidence: 99%